A qualitative and quantitative study of self-reported positive characteristics of individuals with ADHD - Schippers, Lessa M.; Horstman, Lisa I.; Velde, Hans van de; Pereira, Rob Rodrigues; Zinkstok, Janneke; Mostert, Jeanette C.; Greven, Corina U.; Hoogman, Martine (Frontiers in Psychiatry, 2022)
Research in Attention-deficit\hyperactivity disorder (ADHD) has had a clear focus on treatment and the dysfunction in specific situation associated with the condition. However, self-report, observational and anecdotal evidence indicates that there are also positive aspects associated with ADHD. Research on the potential positive features in individuals with an ADHD diagnosis is still limited, especially studies with larger representative samples. Here we performed qualitative research to identify positive aspects and strengths associated with ADHD in a large convenience sample from the Dutch organisation for people with ADHD, dyslexia and dyscalculia. We sent out open-ended questionnaires to the members of the organisation, asking what they consider to be positive aspects of their ADHD. From the responses of individuals with ADHD (n=206), we extracted 116 codes, which were assigned to thirteen subthemes, which in turn led to five themes. These themes were: Creativity, Being dynamic, Flexibility, Socio-affective skills and Higher-order cognitive skills. Core symptoms of ADHD such as impulsivity and hyperactivity were also considered positive aspects of ADHD by a minority of participants. After showing our results to a group of additional individuals with ADHD (focus group) they confirmed the identified positive aspects of ADHD. They also helped us with the interpretation of our findings and mentioned certain positive aspects to be a consequence of living with ADHD (being open minded and being honest). In conclusion, experiencing positive aspects seems to be common in ADHD as almost all participants reported positive aspect of ADHD, these aspects cover many different domains. Awareness about ADHD’s strengths might help individuals with ADHD and their environment to better cope with, accept or embrace their diagnosis and for example make educational or occupational choices that fit them well. To incorporate these positive aspects in the understanding of ADHD, future research should focus on quantifying strengths in ADHD, and on investigating the link between these aspects and clinical characteristics and how this new knowledge can be implemented in psychoeducation and find its way to education and occupational settings.